2018
DOI: 10.1111/jopr.12716
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Gastric Acid Induced Surface Changes on Mechanical Behavior and Optical Characteristics of Dental Ceramics

Abstract: The acid treatment affected the surface roughness, color, and gloss of porcelain and e.max ceramics. The changes in translucency and mechanical strength for all materials were not statistically significant. Zirconia ceramic showed resistance to all treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
39
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(65 citation statements)
references
References 28 publications
11
39
0
8
Order By: Relevance
“…Low pH in a solution containing the dental restorative material has been reported to affect its optical and surface properties (13)(14)(15). In the present study, the conventional mouthwash had a relatively low pH (3.93 AE 0.02).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Low pH in a solution containing the dental restorative material has been reported to affect its optical and surface properties (13)(14)(15). In the present study, the conventional mouthwash had a relatively low pH (3.93 AE 0.02).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the optical and surface properties of these materials can change within the oral cavity. Several studies have reported that acidic solutions, including cola, orange juice, red wine, coffee, and gastric acid, can change the optical properties and surface roughness of toothcoloured dental restorative materials (10)(11)(12)(13)(14)(15). In addition, several oral hygiene solutions currently on the market can also affect the colour of dental restoration materials (16)(17)(18).…”
mentioning
confidence: 99%
“…29 Regarding the surface roughness it was observed that increased surface roughness influences the gloss of the restoration because affect light reflection and color perception due changes in surface topography of the ceramic. 30 Surface roughness increases are directly related to the decrease of the gloss of a specimen, because asperities on its surface will scatter light instead of reflecting it. 9,16,31,32 The gloss of a ceramic may interfere with its ability to reflect light, compromising the optical properties of the restoration and negatively influencing the esthetics.…”
Section: Discussionmentioning
confidence: 99%
“…According to previous reports, a low pH environment (acidic medium) can affect some properties of the porcelain ceramics, such as: surface roughness, color stability, and gloss . Therefore, the acid presence in saliva enables the ceramic surface degradation while the exposure to a basic pH buffer results in segregation of the silica network, resulting in selective ionic leaching of the glass matrix .…”
Section: Introductionmentioning
confidence: 99%